Design and Simulation Studies of Hybrid Power Systems Based on Photovoltaic, Wind, Electrolyzer, and PEM Fuel Cells - Hussein A.Z. AL-bonsrulah; Mohammed J. Alshukri; Lama M. Mikhaeel; Noor N. AL-sawaf; Kefif Nesrine; M.V. Reddy; Karim Zaghib (Energies, 2021)
In recent years, the need to reduce environmental impacts and increase flexibility in the energy sector has led to increased penetration of renewable energy sources and the shift from concentrated to decentralized generation. A fuel cell is an instrument that produces electricity by chemical reaction. Fuel cells are a promising technology for ultimate energy conversion and energy generation. We see that this system is integrated, where we find that the wind and photovoltaic energy system is complementary between them, because not all days are sunny, windy, or night, so we see that this system has higher reliability to provide continuous generation. At low load hours, PV and electrolysis units produce extra power. After being compressed, hydrogen is stored in tanks. The purpose of this study is to separate the Bahr AL-Najaf Area from the main power grid and make it an independent network by itself. The PEM fuel cells were analyzed and designed, and it were found that one layer is equal to 570.96 Watt at 0.61 volts and 1.04 A/Cm2. The number of layers in one stack is designed to be equal to 13 layers, so that the total power of one stack is equal to 7422.48 Watt. That is, the number of stacks required to generate the required energy from the fuel cells is equal to 203 stk. This study provided an analysis of the hybrid system to cover the electricity demand in the Bahr AL-Najaf region of 1.5 MW, the attained hybrid power system TNPC cost was about 9,573,208 USD, whereas the capital cost and energy cost (COE) were about 7,750,000 USD and 0.169 USD/kWh respectively, for one year.